Thrombin activatable fibrinolysis inhibitor and its fibrinolytic effect in normal pregnancy - Mousa, Hatem A.; Downey, Colin; Alfirevic, Zarko; Toh, Cheng-Hock (Thrombosis and Haemostasis, 2004)
We investigated changes in both thrombin activatable fibrinolysis inhibitor (TAFI) antigen levels and its functional effect on in vitro fibrinolysis in normal pregnancy. 152 pregnant women and 31 women in the immediate postpartum period were studied, with pregnancy divided into 6 windows at 4 weekly intervals. As TAFI influences and is in turn influenced by components of the protein C (PC) pathway, its measurements were correlated with levels of soluble thrombomodulin, PC, protein S (PS) and the overall phenotype of activated PC resistance (APCR). Compared with mean TAFI levels at booking gestation (6.6 +1.2 μg/ml), levels peaked at 35-39 weeks gestation (9.6 +2 μg/ml, p = 0.001), followed by a significant drop within 24 hours of delivery (7.2 + 1.1 μg/ml). In functional terms, the mean clot lysis time (CLT) (101 + 13 min at booking) also peaked at 35-39 weeks gestation (141 + 42 min, p = 0.007) and dropped after delivery (99 + 33 min), and was significantly correlated with gestational age (r = 0.410, p = 0.001) and could be abrogated in the presence of an inhibitor to TAFI activation. A significant negative correlation was found between TAFI levels and APCR (r = −0.478, p <0.001), APCRV (r = −0.598; p <0.001), PS (r = −0.490, P <0.001) and PC (r = −0.198, p = 0.02). In summary, there is a significant increase in TAFI levels, which translates into increased CLT during pregnancy. Furthermore, changes in TAFI contribute to the increasing APCR of pregnancy.
Keywords: Thrombin activatable fibrinolysis inhibitor; pregnancy; fibrinolysis; protein C; clot lysis